Choices for living : coping with fear of dying - Langner, Thomas S. (PATH in psychology., 2002)
Although many books are written about bereavement, very few are written about the fear of one's own death and most of these focus chiefly on terminal illness. In contrast, this book looks at the ways in which the fear of death operates on a back burner throughout our lives and how it influences the choices we make and the paths that we follow in life. The author presents a `moral hierarchy' of behavior used in coping with the fear of death and dying.